Translation, data quality, reliability, validity and responsiveness of the Norwegian version of the Effective Musculoskeletal Consumer Scale (EC-17) - Hamnes, Bente; Garratt, Andrew; Kjeken, Ingvild; Kristjansson, Elizabeth; Hagen, Kåre B (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background The Effective Musculoskeletal Consumer Scale (EC-17) is a self-administered questionnaire for evaluating self-management interventions that empower and educate people with rheumatic conditions. The aim of the study was to translate and evaluate the Norwegian version of EC-17 against the necessary criteria for a patient-reported outcome measure, including responsiveness to change. Methods Data quality, reliability, validity and responsiveness were assessed in two groups. One group comprising 103 patients received a questionnaire before and at the end of a self-management programme. The second group comprising 96 patients' received the questionnaire two weeks before and on arrival of the program. Internal consistency and test-retest reliability were assessed. Construct validity was assessed through comparisons with the Brief Approach/Avoidance Coping Questionnaire, (BACQ), the Emotional Approach Coping Scale (EAC) and the General Health Questionnaire (GHQ-20). Responsiveness was assessed with the Standardised Response Mean (SRM). Results Respondents included 66 (64%) and 52 (54%) patients from the first and second groups respectively. Levels of missing data were low for all items. There was good evidence for unidimensionality, item-total correlations ranged from 0.59 to 0.82 and Cronbach's Alpha and test-retest correlations were over 0.90. As hypothesised EC-17 scores had statistically significant low to moderate correlations with the BACQ, EAC and GHQ-20 in the range 0.26 to 0.42. Following the self-management program, EC-17 scores showed a significant improvement with an SRM of 0.48. Conclusion The Norwegian version of the EC-17 has evidence for data quality, internal consistency and test-retest reliability, construct validity and responsiveness to change. The EC-17 seems promising as an outcome measure for evaluating self-management interventions for people with rheumatic conditions, but further studies are needed.